On the Finite Volume Element Method for Self-Adjoint Parabolic Integrodifferential Equations - Mohamed Bahaj; Anas Rachid (Journal of Mathematics)
Finite volume element schemes for non-self-adjoint parabolic integrodifferential equations are derived and stated. For the spatially discrete scheme, optimal-order error estimates in , , and , norms for are obtained. In this paper, we also study the lumped mass modification. Based on the Crank-Nicolson method, a time discretization scheme is discussed and related error estimates are derived.